Ausencia paterna y la salud afectiva en los niños del CIBV Capullitos de Amor, sector ciudad del norte - Parrales Morales, Dayton Jazmany (2019)
Society thinks that when parents work and provide everything material to their children they are good parents or their children are satisfied, if they not only focus on the work but also on what their children feel and want from them, the parental absence would feel less. The parental absence came by the abandonment of the parents or the disinterest of them at the time of educating them and giving them affection so that they develop in an adequate way and manage to create an adequate future. Children who are formed with a single parent are at greater risk of developing emotional or mental problems, antisocial behavior, and irresponsibility. They are three times more likely to have problems with friendships Seventy percent of young offenders come from single-parent families. Children who grow up in a single-parent home have almost double the rate of abuse, and more than double the chances of ending up in jail. On the other hand, affective health is defined as the different emotions that a person can demonstrate in different situations. Affective health, then, is the health that human beings need to have in order to enjoy everything around them and to transmit to other human beings their emotions that manifest from their interior to their exterior, resulting in many intentions of being nice to others, cordial, show attachment to good social relations. etc., In the present investigation the consequences of the paternal figure will be focused, trying to identify the incidence of the affective factors in the children of the CIBV Capullitos de Amor, in order to reduce the presence of challenges in the socio affective and psychological areas, concluding with a proposal where guidelines are established to improve the work that is being developed in said children's center.